2015
DOI: 10.1001/jamaoto.2014.2626
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Orbital Complications of Pediatric Rhinosinusitis in the United States

Abstract: The public health impact of orbital complications of pediatric rhinosinusitis continues to be substantial. Since the institution of the PCV-7 vaccine, national trends demonstrate a slightly decreased prevalence of hospital admissions. However, there is a shifting trend toward an older age at admission and a higher proportion of children undergoing surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Additionally, 25% of patients in our study with orbital complications underwent sinus procedures, in agreement with previous data showing increasing rates of surgical intervention in management of orbital complications of sinusitis. 6 As expected, our data corroborated that total LOS and THC were higher in patients undergoing sinus procedures than those who did not. 7,15 We felt comparison of LOS after surgery for those undergoing procedures with total LOS for those who did not was a more meaningful comparison of LOS associated with each treatment modality.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, 25% of patients in our study with orbital complications underwent sinus procedures, in agreement with previous data showing increasing rates of surgical intervention in management of orbital complications of sinusitis. 6 As expected, our data corroborated that total LOS and THC were higher in patients undergoing sinus procedures than those who did not. 7,15 We felt comparison of LOS after surgery for those undergoing procedures with total LOS for those who did not was a more meaningful comparison of LOS associated with each treatment modality.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, the preventive treatment of complicated acute sinusitis must go through the management of viral rhinopharyngitis since they constitute the front door of sinusitis in most cases, and therefore that of complications. No study to date has investigated the role of vaccines through the general route in preventing the acute rhino-sinus infection of the child [32]. It is likely that the Hib conjugated vaccines (1992) and Heptavalent conjugated pneumococcus are induced by reducing the nasopharyngeal carriage of vaccine serotypes and their transmission, an individual but also collective protection [31] [33].…”
Section: Discussionmentioning
confidence: 99%
“…Referral and evaluation by an otolaryngologist for any complicated sinus infection is indicated due to a potential for rapid progression of disease even with antibiotic therapy. However, it has been shown that even in the setting of a subperiosteal abscess (Chandler class III), successful treatment can be accomplished in 93 % of children with medical management alone [29,30]. Medical management is most successful for Chandler class I or early class II, but all pediatric patients with acute sinusitis with orbital involvement require close observation by an otolaryngologist for possible surgical drainage of the sinuses.…”
Section: Complications Of Acute Rhinosinusitismentioning
confidence: 99%